Nitrogen-doped 3D porous carbons with iron carbide nanoparticles encapsulated in graphitic layers derived from functionalized MOF as an efficient noble-metal-free oxygen reduction electrocatalysts in both acidic and alkaline media. Issue 112 (22nd November 2016) - Xue, Juanhong; Zhao, Ling; Dou, Zhiyu; Yang, Yan; Guan, Yue; Zhu, Zhen; Cui, Lili
Abstract : Functionalized 3D porous carbons comprising encased iron carbide species, derived from a MOF, display outstanding ORR performance in both acidic and alkaline solutions. Abstract : A novel kind of functionalized metal organic framework (F-MOF, Prussian blue/graphene oxide composite, PB/GO) is prepared by a simple method. The morphology characterization indicates that iron carbide nanoparticles supported on highly nitrogen-doped 3D porous carbons (Fe–C/NG) are formed after direct annealing of F-MOF under an Ar atmosphere. Fe–C/NG-10%-700-AL (10% represents the mass ratio between GO and iron salt; 700 stands for pyrolysis temperature; AL means acid leaching) exhibits excellent catalytic activity for the ORR (oxygen reduction reaction) in both acidic and alkaline media, together with superior durability, excellent methanol tolerance and a nearly four-electron pathway for the ORR. The excellent catalytic performance for the ORR on Fe–C/NG-10%-700-AL is attributed to the existence of iron carbide nanoparticles, highly doped N concentration, high surface area and pores of 3D graphene and the synergistic effect between multiple components.